Implementasi Metode Weighted Product Dan Fuzzy C-Means Dalam Pemilihan Peminatan Jurusan Pada SMA Perguruan Rakyat 2 - Riana, Eri (STMIK Budi Darma, 2018)
As per the rules applicable curriculum in Indonesia, high school students of class X to class XI up to experience election majors. Majors are available in the high school fields of interest include Natural Sciences, Social Sciences, and Linguistics. Majors will be tailored to students' abilities in areas of interest that exist, the goal for later in life, lessons are given to students to be more focused because it was in accordance with the ability of the field of interest. One of the considerations for selecting students are majors in determining student achievement in semester one and two (class X) in the form of scores. Lack of accuracy of the electoral process in the majors with the manual system of high school led to the need for the use of computational methods for grouping students majoring in the electoral process. Weighted Product Method and Fuzzy C-Means is a method that is easy and often used in the data grouping technique for making an estimate that is efficient and does not require a lot of parameters. Several studies have concluded that the method of Weighted Product and Fuzzy C-Means can be used to classify data based on certain attributes. This research will be used Weighted Product method and Fuzzy C-Means to cluster the data based on high school students value the core subjects for the majors. This study also tested the accuracy of the method and the Product Weighted Fuzzy C-Means in determining the majors in high school.